TRADISI DAN KEARIFAN LOKAL DALAM PEMBUATAN MINUMAN MOKE DI KABUPATEN SIKKA: STUDI KASUS PROSES PEMBUATAN DAN NILAI-NILAI BUDAYA YANG TERKANDUNG - Hadi Jaya Putra, Sukarman; Densiana Keron, Marselina; Kuki, Maria; Theo, Agustinus; Bura, Yuventa; Agnes Neang, Avelina; Yanti, Gormia; Mude, Marsel; Bernadus Mitan, Tekla; Yosefin Koltafia, Ativelna; Yunita Rugun, Maria; Theresia Tandi, Rofina; Bonefasia, Margaretha; Ursulina Uni, Maria; Demus Bobi, Mikhael (Universitas Cokroaminoto Palopo, 2024)
This research aims to reveal the cultural, social and economic values ​​contained in the tradition of making moke. With a qualitative approach, data was collected through in-depth interviews with community leaders, observation of the manufacturing process, and active participation in traditional activities. The research results show that moke has an important role in various traditional ceremonies and community social life. Making moke strengthens social relations between residents and is a source of income for many families in Riit Village. Moke also plays a symbolic role in honoring ancestors and maintaining social unity. The practice of making moke reflects local wisdom passed down through generations, demonstrating a wealth of skill and knowledge in this process. Even though it has high economic value, moke consumption must be monitored to avoid negative impacts.